2014
DOI: 10.1002/hed.23783
|View full text |Cite
|
Sign up to set email alerts
|

Enchondroma of the nasal septum due to Ollier disease: A case report and review of the literature

Abstract: Surgery remains the only effective solution in removing an enchondroma and preventing the tendency toward malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…To the best of our knowledge, this was one of the rarest case of nasal enchondroma in a patient of Maffucci syndrome with only two such cases reported in the literature till now. 4,5 We got a computed tomography (CT) of paranasal sinuses PNS, which confirmed our clinical findings. The CT-PNS was suggestive of well-defined expansile nasal mass approximately 3 × 2 cm in size in left nasal cavity with epicenter in nasal septum, pushing on left lateral nasal wall with smooth pressure erosions on left half of hard palate and right-sided middle and inferior turbinate (Figs 5A and B).…”
Section: Aijcrsupporting
confidence: 77%
See 1 more Smart Citation
“…To the best of our knowledge, this was one of the rarest case of nasal enchondroma in a patient of Maffucci syndrome with only two such cases reported in the literature till now. 4,5 We got a computed tomography (CT) of paranasal sinuses PNS, which confirmed our clinical findings. The CT-PNS was suggestive of well-defined expansile nasal mass approximately 3 × 2 cm in size in left nasal cavity with epicenter in nasal septum, pushing on left lateral nasal wall with smooth pressure erosions on left half of hard palate and right-sided middle and inferior turbinate (Figs 5A and B).…”
Section: Aijcrsupporting
confidence: 77%
“…There are only two case reports that describe a primary involvement of the nasal cavities and paranasal sinuses (PNS). 4,5 It results from deregulated proliferation and differentiation of chondrocytes during physiological enchondral ossification. 3 Complications include spontaneous fracture, resulting in skeletal deformity and high risk of malignant transformation in up to 40% of the cases.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Maffucci syndrome, Ollier disease lacks the clinical manifestation of hemangioma and typically presents unilaterally. Imaging studies of patients with Ollier disease have demonstrated that there is generally no venous stone in the hemangioma and previously published studies reported that the probability of chondroma malignant transformation in Ollier disease was low ( 20 , 21 ). Furthermore, Maffucci syndrome needs to be distinguished from other diseases characterized by similar vascular malformations, such as blue rubber bleb nevus syndrome, Klippel-Trenaunay syndrome and glomuvenous malformations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 3 ] They most commonly affect the long bones of the hand, followed by the flat bones, and predominantly occur in the tubular bones. [ 4 ] Enchondroma protuberans is a rare type of enchondroma, defined as an exophytic enchondroma of bones because of its location; the phalanges or metacarpal bones are the most common location involved. [ 5 , 6 ] The main difference between enchondroma protuberans and the conventional enchondroma is the protruded mass.…”
Section: Introductionmentioning
confidence: 99%